2011
DOI: 10.1111/j.1471-0528.2011.03100.x
|View full text |Cite
|
Sign up to set email alerts
|

To what extent are national guidelines for the management of urinary incontinence in women adhered? Data from a national audit

Abstract: Objective To assess the degree of adherence to the current National Institute for Health and Clinical Excellence (NICE) guidelines on the management of urinary incontinence (UI) in women.Design Retrospective survey of consecutive female inpatients and outpatients with UI as part of a national audit.Setting NHS hospital and primary care (PC) trusts.Population or sample Twenty-five women <65 years old and 25 women ‡65 years old from each participating site.Method All NHS trusts in England, Wales and Northern Ire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 15 publications
0
41
2
Order By: Relevance
“…The US government sets minimum quality standards for UI assessment and management in long‐term care, but these standards, along with basic fundamental principles of UI, are poorly understood by long‐term staff . Two groups, the US Assessing Care of Vulnerable Elders (ACOVE) project and the UK Clinical Effectiveness and Evaluation Unit, have developed quality performance measures for UI care in frail older people, using structured literature and expert panel review . It should be borne in mind that multiple diagnoses can co‐exist, and due consideration given to mixed UI, combining urge and stress elements, and detrusor hyperactivity with impaired contractility (DHIC) …”
Section: Assessment Of the Frail Older Patient With Incontinencementioning
confidence: 99%
“…The US government sets minimum quality standards for UI assessment and management in long‐term care, but these standards, along with basic fundamental principles of UI, are poorly understood by long‐term staff . Two groups, the US Assessing Care of Vulnerable Elders (ACOVE) project and the UK Clinical Effectiveness and Evaluation Unit, have developed quality performance measures for UI care in frail older people, using structured literature and expert panel review . It should be borne in mind that multiple diagnoses can co‐exist, and due consideration given to mixed UI, combining urge and stress elements, and detrusor hyperactivity with impaired contractility (DHIC) …”
Section: Assessment Of the Frail Older Patient With Incontinencementioning
confidence: 99%
“…The study was applicable to all people with lower urinary tract symptoms (voiding and storage disorders), bladder and bowel dysfunction, urinary incontinence and faecal incontinence. Results from the audit of faecal incontinence [10] and those for urinary incontinence in women [11] have been reported elsewhere. Patients were suitable if aged 18 or over; sufficient time had elapsed to allow assessment and formulation of a management plan; a catheter was inserted for urinary incontinence rather than retention; and incontinence was either an old or a new complaint.…”
Section: Methodsmentioning
confidence: 96%
“…Even in extreme case scenarios our results appeared to be rather robust and the implementation of the OCSS new care strategy remained cost-saving compared to usual care. Several studies [12][13][14] indicated areas for improvement in the management and treatment of urinary incontinence. Our results show that improvement of care pathways by implementing a continence nurse specialist not only results in better clinical outcomes but also contributes to important cost-savings.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies [12][13][14] have indicated areas for improvement in the management and treatment of urinary incontinence, especially in elderly living in the community. The Optimum Continence Service Specification (OCSS) was developed in order to improve urinary incontinence care in different healthcare settings for four different incontinence patient profiles: i) stress and urgency urinary incontinence, ii) faecal incontinence, iii) neurological induced incontinence, and iv) urinary incontinence in the elderly/ cognitively impaired [15].…”
Section: Introductionmentioning
confidence: 99%